The 600 kidney transplants performed at the Botucatu Medical School Hospital - UNESP: changes over - de Andrade, Luis G.ustavo Modelli; Garcia, Paula D.alsoglio; Contti, Mariana M.oraes; da Silva, Andre L.opes; Banin, Vanessa B.urgugi; Duarte, Juliana da Cunha; de Carvalho, Maria F.ernanda Cordeiro (My University, 2014)
INTRODUCTION: A progressive improvement in kidney transplant outcomes has been achieved over the last decades. OBJECTIVE: To determine the degree to which this has occurred in our center, we conducted an outcome analysis of our kidney transplant program during three different time periods, especially focusing on patient and graft survival. METHODS: The 600 kidney transplants performed at Botucatu Medical School/UNESP up to December 2011 were examined. Three different time periods were chosen to correspond with major shifts in immunosuppressant usage: Era 1 (1987-2000), cyclosporine and azathioprine usage (n = 180); Era 2 (2001-2006), cyclosporine and mycophenolate mofetil usage (n = 120); and Era 3 (2007-2011), tacrolimus and mycophenolate (n = 300). RESULTS: Compared with the first era, mean recipient age, diabetes prevalence, and the number of living donor transplantations (60%) were increased in the third era. Induction therapy was used in 75% of the cases in Era 3, 46.6% in Era 2, and in 3.9% in Era 1 (p < 0.0001). The mean number of transplants/year rose from 14 in Era 1 to 75 in Era 3. Overall survival according to donor type was similar to that reported in the literature. Five-year graft survival following deceased donor transplantation progressively increased from 13.1% (Era 1) to 81.9% (Era 3). CONCLUSION: Significant differences were observed over time. The percentage of living donors decreased as that of deceased donors increased. Survival after deceased donor transplants was greatest in Era 3, probably due to the improved experience of the medical team, and to the use of tacrolimus and mycophenolate mofetil combination with induction.